Carotenoid Interactions with PCSK9: Exploring Novel Cholesterol-Lowering Strategies - Alessandro Medoro; Giovanni Scapagnini; Simone Brogi; Tassadaq Hussain Jafar; Truong Tan Trung; Luciano Saso; Sergio Davinelli (Pharmaceuticals)
Background/Objectives: This study investigated the potential of green algae-derived carotenoids as natural inhibitors of the proprotein convertase subtilisin/kexin type 9 (PCSK9), a key regulator of cholesterol metabolism. PCSK9 promotes the degradation of low-density lipoprotein receptors (LDLR), thereby increasing blood cholesterol levels and elevating the risk of cardiovascular diseases. Methods/Results: We screened the pharmacophore fit score of 27 carotenoids with PCSK9 and identified 14 that were analyzed for binding affinity and molecular interactions. Astaxanthin, siphonaxanthin, and prasinoxanthin were identified as the top candidates, demonstrating strong binding affinity (−10.5, −10.3, and −9.4 Kcal/mol, respectively) and stable interactions with several known key residues within the active site of PCSK9, including Pro-331, Arg-357, Cys-358, Val-359, Asp-360, Ile-416, Leu-436, Thr-437, Pro-438, Leu-440, Arg-458, Val-460, Trp-461, Arg-476, Cys-477, Ala-478, Ala-649, Val-650, and Asp-651. Density functional theory analysis confirmed the stability of astaxanthin and its favorable electronic properties, suggesting its potential as an effective inhibitor. Molecular dynamics simulations of the PCSK9–astaxanthin complex revealed sustained structural stability and key interactions critical for maintaining the functional integrity of the protein. Conclusions: These findings provide evidence that specific carotenoids, particularly astaxanthin, may offer a cost-effective alternative to existing PCSK9 inhibitors, providing a potential approach for managing cholesterol levels and reducing cardiovascular risk. Pre-clinical and clinical validations are required to confirm the therapeutic potential of these compounds.